Swear Words Translation in The Raid Movie and Its Classification - Evandio Zefanya Pattiselanno (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study wanted to help the reader to understand about the classification of swear words in “The Raid” movie’s dialogue. The writer used Larson’s (1984) kinds of translation (literal and idiomatic translation). The writer was interested in analyzing the swear words, especially the classification of translation whether it match to the original meaning or not, for example “anjing” becomes “dog”, “bajingan” becomes “bastard” or being translated using different swear words in the English subtitle of the movie. The writer found that there are so many dialogues translated using swear words on the subtitle of the movie while the dialogue itself does not have any swear words. The rest of other swear words are being translated match with its original meaning, and there are also different translation. Keywords: translation, swear word, subtitle, literal translation, idiomatic translation